The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3171/2020.5.focus20289
|View full text |Cite
|
Sign up to set email alerts
|

Association of osteopenia and osteoporosis with higher rates of pseudarthrosis and revision surgery in adult patients undergoing single-level lumbar fusion

Abstract: OBJECTIVEPatients with osteopenia or osteoporosis who require surgery for symptomatic degenerative spondylolisthesis may have higher rates of postoperative pseudarthrosis and need for revision surgery than patients with normal bone mineral densities (BMDs). To this end, the authors compared rates of postoperative pseudarthrosis and need for revision surgery following single-level lumbar fusion in patients with normal BMD with those in patients with osteopenia or osteoporosis. The secondary outcome was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 13 publications
0
28
0
1
Order By: Relevance
“…It has been well proven that surgical complications, such as instrument failure (cage migration, screw loosening, and pseudarthrosis) and subsequent vertebral compression fractures, correlate with osteoporosis. 24,25 Both PS loosening and cage migration are correlated with an increase in back pain, rate of nonunion, and pseudarthrosis, leading to poor quality of life. 26,27 In the treatment of elder patients with osteoporotic LDD, many surgical techniques have hsve shown satisfactory fusion rates and good stability, including cement augmentation of PS, expandable PSs, and CBT-screw fixation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well proven that surgical complications, such as instrument failure (cage migration, screw loosening, and pseudarthrosis) and subsequent vertebral compression fractures, correlate with osteoporosis. 24,25 Both PS loosening and cage migration are correlated with an increase in back pain, rate of nonunion, and pseudarthrosis, leading to poor quality of life. 26,27 In the treatment of elder patients with osteoporotic LDD, many surgical techniques have hsve shown satisfactory fusion rates and good stability, including cement augmentation of PS, expandable PSs, and CBT-screw fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking, metabolic disorders, surgical instrumentation and technique, and fusion location have been demonstrated as the risk factors for pseudarthrosis ( 103 , 104 ). In addition to this, osteopenia and osteoporosis have been suggested as another risk factor for pseudarthrosis, and implant failure, such as screw loosening ( 105 , 106 ). Post-operative back pain was reported in the patients undergoing lumbar fusion procedures.…”
Section: Non-surgical Treatment—the Foremost Option For Ldh Patients ...mentioning
confidence: 99%
“…Optimizing medical conditions prior to spine surgery is being increasingly performed to improve outcomes, and avert adverse events [19]. Khalid, et al [20] reported higher rates of postoperative pseudoarthrosis and revision surgery following a single-level lumbar spinal fusion in patients with osteopenia and osteoporosis compared to patients with normal Bone mineral densities (BMD). The authors note that pretreatment with medications to prevent bone loss prior to surgery decreased complication rates.…”
Section: Corpectomymentioning
confidence: 99%